O cotidiano de um serviço de urgência e emergência nos discursos de usuários e trabalhadores - Daniela Soares Santos (2015)
This study set out to examine the discourses of users and professionals on the everyday life services provided by urgent and emergency care units of a public hospital in Belo Horizonte, State of Minas Gerais, Brazil. It is a qualitative study, using the post-structuralism framework that tends to question reality, who individuals are and how they relate to society. The data was gathered by observing the everydayservices of the units and by conducting semi-structured interviews with users and healthcare professionals, administrative and support staff of the urgent and emergency care units who assist and provide services to the users. The data produced by the interviews was studied through the Discourse Analysis. The results show that although most users criticize access and service conditions, they do not criticize those services more because, due to their view on the reality of the public health system, that Emergency Care Unit is better than the others because they can get access to it, schedule medical appointments in several specialties and also undergo complementary tests. The service is also viewed as better when compared to situations they have experienced in other healthcare units. It is not much, but it is what they can get access to and they feel guilty for criticizing the same service unit that received them. Concerning healthcare professionals, there is a consensus of opinion on the existing high demand entering the Emergency Care Units and frequent overcrowding. Additionally, they stress the need for agility and professional training to provide services in urgent and emergency cases. Nevertheless, those discourses are undermined as they report actual scarcities witnessed every day in these units. In this study, everyday life means "what is given to us every day", where we produce and reproduce social customs, a place of existence, the issues of routine life andeveryday practices represent socially organized ways of living in a given time and space. Thus, it is believed that understanding the views of users and professionals regarding healthcare demands and their needs, and meeting the daily demands of the service can contribute to reorganize the institutional micropolitics, create measures toimprove the work, optimize services and reduce errors, among others. Recognizing this dimension can show user satisfaction with the units and staff satisfaction with the work and quality they offer.